Steel non-orthogonal reduced beam section moment connections-a case study - Ball, Steven C. (The structural design of tall and special buildings, 2011)
SUMMARY The architectural expressions for many modern buildings require creative and unconventional structural solutions. Columns must be taller, beams must span further, the structure must be more slender, elements must be curved, structural framing must be sloped and connections must deviate from conventional orthogonal fit‐up. Although the technology exists to analyze and design responsive structural systems, prescriptive code requirements oftentimes hinder the implementation of those technologies. Although not a ‘tall building’ by traditional definition, the Tom Bradley International Terminal (TBIT) Modernization Program at Los Angeles International Airport (LAX) provides an appropriate case study in the implementation of unconventional structural geometry subject to code requirements that prescribe contrasting conventional geometry, which is a familiar challenge for many tall buildings. The architectural expression for the LAX TBIT Modernization Program required the use of long‐span steel Special Moment Frames with non‐orthogonal moment connections between the beams and columns. The beams were sloped, some were sloped and curved and some of the columns were sloped. The reduced beam section (RBS) moment connection was selected for the project. ANSI/AISC 358, Prequalified Connections for Special and Intermediate Steel Moment Frames for Seismic Applications, provides prequalification limits for using an RBS connection. Those limits do not address non‐orthogonal moment connections. ANSI/AISC 358 implicitly limits connections to orthogonal geometry; hence, non‐orthogonal moment connections are not prequalified for use in seismic applications. This paper describes the structure and the cyclic testing program that was implemented to qualify the proposed non‐orthogonal RBS connections in accordance with ANSI/AISC 341, Seismic Provisions for Structural Steel Buildings, Appendix S for use on the LAX TBIT Modernization Project. Copyright © 2011 John Wiley & Sons, Ltd.